2022
DOI: 10.1038/s42003-022-04156-4
|View full text |Cite
|
Sign up to set email alerts
|

A critical bioenergetic switch is regulated by IGF2 during murine cartilage development

Abstract: Long bone growth requires the precise control of chondrocyte maturation from proliferation to hypertrophy during endochondral ossification, but the bioenergetic program that ensures normal cartilage development is still largely elusive. We show that chondrocytes have unique glucose metabolism signatures in these stages, and they undergo bioenergetic reprogramming from glycolysis to oxidative phosphorylation during maturation, accompanied by an upregulation of the pentose phosphate pathway. Inhibition of either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…In support of this, these cells were enriched for pathways related to connective tissue replacement, cytokine production, and positive regulation of chemotaxis, which aligns with the secretion of angiogenic and osteoclastogenic signals by hypertrophic chondrocytes during endochondral ossification to promote vascular and osteoclast invasion into degrading cartilage [ 68 ]. Genes associated with the regulation of glycolytic and sugar metabolism pathways were also enriched; this is notable as glycolysis and oxidative phosphorylation dynamics vary at different stages of chondrocyte differentiation [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…In support of this, these cells were enriched for pathways related to connective tissue replacement, cytokine production, and positive regulation of chemotaxis, which aligns with the secretion of angiogenic and osteoclastogenic signals by hypertrophic chondrocytes during endochondral ossification to promote vascular and osteoclast invasion into degrading cartilage [ 68 ]. Genes associated with the regulation of glycolytic and sugar metabolism pathways were also enriched; this is notable as glycolysis and oxidative phosphorylation dynamics vary at different stages of chondrocyte differentiation [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we also visualized the expression of genes in M8 by heatmap and bar plot, the results showed that only IGF2 was significantly up‐regulated in basal state of oral mucosa (Figure 2E,F ). IGF2 is one of the earliest discovered imprinted genes, which plays an important role in promoting cell differentiation, proliferation, and embryonic growth and development, 16 but the role of IGF2 in skin wound healing has not been fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…An important factor in maintaining the balance between glycolysis and OXPHOS is IGF2. Hypertrophic chondrocytes from IGF2 −/− mice enhance their OXPHOS and pentose phosphate pathways [90]. Protein and lipid components, as well as nucleotide precursors, are required to ensure the anabolic boost of the hypertrophic state [90,91].…”
Section: Central Metabolic Pathways' Reprogramming and Mitochondrial ...mentioning
confidence: 99%
“…Hypertrophic chondrocytes from IGF2 −/− mice enhance their OXPHOS and pentose phosphate pathways [90]. Protein and lipid components, as well as nucleotide precursors, are required to ensure the anabolic boost of the hypertrophic state [90,91]. The first, oxidative phase of the pentose phosphate pathway produces NADPH + H + and pentoses, which can be incorporated into nucleic acids; when the second, non-oxidative phase also occurs, only NADPH + H + remains as the sole reaction product.…”
Section: Central Metabolic Pathways' Reprogramming and Mitochondrial ...mentioning
confidence: 99%